Peradilan Berpancaran “Sinar Ketuhanan”: Mahkamah Konstitusi Dalam Masa Kepemimpinan Arief Hidayat (2015-2017) - Bisariyadi Bisariyadi (Jurnal Hukum IUS QUIA IUSTUM, 2020)
Almost every Chief Justice of the Constitutional Court has jargon carried during theis leadership. Arief Hidayat, during his reign, often put forward the term "divine light". This term is closely related to Pancasila as the ideology of the state and religion. Therefore, the purpose of expressing jargon during the leadership of a Chief Justice of the Constitutional Court must have strategic value. Moreover, when the discourse is concerned with the classic problem in finding the relationship between religion and the state. However, there is no academic study that traces the purpose of the term "divine light" as stated by Arief Hidayat. This paper intends to fill in the gap by using normative research methods and legal comparisons. The discussion in writing this article is divided into three parts. First, it reviews the normative and theoretical side of the relationship between religion and constitutionalism. Second, we will look at Arief Hidayat's background to be able to find the meaning of the term "divine light" that he uses. The last part of this paper is to examine the decisions of the Constitutional Court which contain the term "divine light" in order to seek an official interpretation of Arief Hidayat's thoughts about the divine light.